Emergence of carbapenem- and tigecycline-resistant Klebsiella pneumoniae ST617. (June 2022) - Sun, Lin; Xu, Gang; Nan-Meng,; Li, Gui-Ling; Wang, Zhen-Yu; Mei, Cai-Yue; Jiao, Xinan; Wang, Jing
Highlights: Co-resistance to carbapenem and tigecycline was observed in Klebsiella pneumoniae ST617. The bla KPC-2 gene was located in a conjugative plasmids associated with a commonly observed core structure. The tet (A) variant may account for tigecycline resistance.